2021
DOI: 10.15789/1563-0625-ipo-2170
|View full text |Cite
|
Sign up to set email alerts
|

Immunoregulatory potential of pregnancy-specific β1-glycoprotein

Abstract: The embryo, being half an antigenically “foreign” organism, should elicit a maternal immune response. During evolution, however, the mechanisms ensuring successful development of pregnancy have been formed. In particular, among factors providing immune tolerance during pregnancy are some proteins associated with pregnancy. The pregnancy-specific β 1-glycoprotein (PSG, PSG1; SP1; PSβG1) is a dominant fetoplacental protein produced by cyto- and syncytiotrophoblast cells, and it exhibits immunosuppressive propert… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 63 publications
0
2
0
2
Order By: Relevance
“…Human PSG was obtained using the authors' patented method of immunopurification with the biospecific sorbent and subsequent cleaning from the immunoglobulin contamination with HiTrap Protein G HP column (Amersham Biosciences) [1]. Physiological concentrations of PSG corresponding to maternal peripheral blood concentrations during pregnancy, namely 1, 10, and 100 µg/ml (first, second, and third trimester, respectively) [3], were used in experiments.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Human PSG was obtained using the authors' patented method of immunopurification with the biospecific sorbent and subsequent cleaning from the immunoglobulin contamination with HiTrap Protein G HP column (Amersham Biosciences) [1]. Physiological concentrations of PSG corresponding to maternal peripheral blood concentrations during pregnancy, namely 1, 10, and 100 µg/ml (first, second, and third trimester, respectively) [3], were used in experiments.…”
Section: Methodsmentioning
confidence: 99%
“…Pregnancy-specific β1-glycoprotein (PSG) is a predominant fetoplacental protein produced by cyto-and syncytiotrophoblast cells and possesses various immunoregulatory effects [3]. We have earlier demonstrated that native PSG preparation could regulate the molecular-genetic factors governing the differentiation of immune memory T cells.…”
mentioning
confidence: 99%
“…PSG) является доминирующим фетоплацентарным белком, обладающим иммуномодулирующими свойствами. За последние 10 лет, благодаря разработке авторского метода получения нативного препарата ТБГ человека [1], мы продемонстрировали эффекты этого белка в отношении различных популяций иммунных клеток [10]. Было установлено, что ТБГ стимулирует экспрессию IDO моноцитами женщин, подавляет пролиферацию и дифференцировку Th17, подавляет продукцию провоспалительных цитокинов (IL-8, IL-17, IFNγ, MCP-1, TNFα) а также G-CSF и GM-CSF [10].…”
Section: Introductionunclassified
“…За последние 10 лет, благодаря разработке авторского метода получения нативного препарата ТБГ человека [1], мы продемонстрировали эффекты этого белка в отношении различных популяций иммунных клеток [10]. Было установлено, что ТБГ стимулирует экспрессию IDO моноцитами женщин, подавляет пролиферацию и дифференцировку Th17, подавляет продукцию провоспалительных цитокинов (IL-8, IL-17, IFNγ, MCP-1, TNFα) а также G-CSF и GM-CSF [10]. Помимо этого, было установлено, что ТБГ угнетал экспрессию маркеров активации CD28 и CD25 наивными Т-клетками, не влияя на продукцию ими IL-2, однако на уровне Т-клеток иммунной памяти ТБГ снижал поверхностную экспрессию CD25 одновременно со снижением продукции IL-2.…”
Section: Introductionunclassified